Effect of Seasonal Variation on Nitrate Contents In Natural Sal Forest (Shorea robusta) - Pokhriyal, T. C.; Ramola, B. C.; Bisht, M. S.; Nautiyal, H. O.; Unnikrishnan, K. P. (Indian Forester, 1988)
Nitrate contents in the leaf, litter and soil upto 60 cm depth were investigated in the natural sal (Shorea robusta) forest, Jhajra, DehraDun. Significantly more soil nitrate was observed in the upper depths (0-30 cm) as compared to 30-60 cm depth. The nitrate contents in the top and middle portion of canopy were significantly higher as compared to the nitrate content in the bottom portion. The nitrate content in the leaves have also responded to the seasonal variations. Though there was no significant correlations observed among the variables when data was pooled for the whole year, significant correlations were available within the seasons.